2016
DOI: 10.1177/1071100716634791
|View full text |Cite
|
Sign up to set email alerts
|

Increased Reduction Clamp Force Associated With Syndesmotic Overcompression

Abstract: Level III, case-control series, in accordance with STROBE guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…This suggests that there was a net compression effect or medial translation, rather than rotational malreduction. This finding is consistent with studies by Haynes et al [ 28 ] and Cherney et al [ 29 ] that showed overcompression was likely during reduction clamping of the syndesmosis, with a mean of 1 mm of overcompression and 5° of external rotation. Similar results were found in a cadaveric study by Phisitkul et al [ 25 ], which showed a mean syndesmosis displacement of 0.1 ± 0.77 mm in all degrees of instability and overcompression of 0.93 ± 0.70 mm during clamping, with the clamp in the neutral anatomical axis.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that there was a net compression effect or medial translation, rather than rotational malreduction. This finding is consistent with studies by Haynes et al [ 28 ] and Cherney et al [ 29 ] that showed overcompression was likely during reduction clamping of the syndesmosis, with a mean of 1 mm of overcompression and 5° of external rotation. Similar results were found in a cadaveric study by Phisitkul et al [ 25 ], which showed a mean syndesmosis displacement of 0.1 ± 0.77 mm in all degrees of instability and overcompression of 0.93 ± 0.70 mm during clamping, with the clamp in the neutral anatomical axis.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies by the senior author (MJG) have sought to promote the safe use of reduction clamps to generate an indirect reduction, by optimizing both proper clamp tine positioning 44 and reduction force. 28 Despite the conclusions in this study, some surgeons will still choose to avoid opening the syndesmosis routinely and are more comfortable with an indirect reduction technique. Additionally, other scenarios (e.g.…”
Section: Discussionmentioning
confidence: 79%
“…Indirect reduction at all positions was performed by a single observer with experience in generating approximately 130 N/m of force with reduction forceps in an effort to standardize the reduction force magnitude. 28 The indirect reduction at each location was performed such that the syndesmosis was not exposed to the observer for visual inspection, nor was there an attempt at radiographic reduction assessment prior to the CT being performed at the specified clamped location. After the specimen was imaged at each clamping position, the screws were removed and the unstable syndesmosis was then reduced using the surgeon’s thumb alone as manual digital pressure, while simultaneously palpating the anterior tibiofibular relationship for congruency.…”
Section: Methodsmentioning
confidence: 99%
“…Overcompression is considered to be related to the force of compression applied with a clamp or the position of the ankle joint during reduction. Haynes et al (17) demonstrated a significant correlation between increased clamp force and syndesmotic overcompression and determined the objective forces that lead to overcompression. Abbreviations: BMI, body mass index; PER, pronation external rotation; SER, supination external rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Although most institutions have enough instruments, concern exists regarding the availability of these items. In addition, overcompression was frequently observed with the use of a reduction clamp (9,17). Although Tornetta et al (18) found no limitation in ankle dorsiflexion despite maximum syndesmotic overcompression in a cadaveric study, the clinical result of this observation is uncertain.…”
mentioning
confidence: 99%